New material of the Late Cretaceous marine turtle Ctenochelys acris Zangerl, 1953 and a phylogenetic reassessment of the 'toxochelyid'-grade taxa. (3rd August 2017) - Gentry, Andrew D.
Abstract : Late Cretaceous marine turtles formerly referred to the family Toxochelyidae represent perhaps the earliest members of the clade including extant marine species of cryptodire (Chelonioidea). Though more pelagically specialized marine taxa such as Protostegidae (i.e. Archelon, Desmatochelys ) predate the first occurrence of any known 'toxochelyid' species, phylogenetic analyses of modern and fossil Testudines have shown that the protostegids may be a separate radiation of stem cryptodires only distantly related to modern marine turtles. This hypothesis has since been supported by ancillary evidence from the stratigraphic record and has been argued from a perspective of rampant homoplasy. This information brings into question our understanding of chelonioid evolution with regard to their previously assumed monophyly, and supports the placement of 'toxochelyids' as perhaps the earliest definitive members of total group Chelonioidea (Pan-Chelonioidea). However, many 'toxochelyids' are known from partial holotypes, preventing accurate species diagnosis and precluding these species from character-based phylogenetic analyses. A poorly known member of this clade, Ctenochelys acris, is herein redescribed based on several nearly complete specimens from the early Campanian Mooreville Chalk of Alabama. Ctenochelys acris is characterized by large, dorsolaterally oriented orbits, significant contributions of the palatines to the secondary palate, a broad maxillary triturating surface, and almost equilaterally pentagonal posterior peripherals. This redescription not only identifies previously unknown apomorphies of Ctenochelys spp. but also provides an opportunity to examine the 'toxochelyids' within a global phylogenetic context. A constraint tree reflecting the recognized molecular topology for extant Testudines is used as a backbone and the resulting phylogeny is then placed within a chronostratigraphic framework in an effort to present a scenario that reconciles anatomical, temporal and phylogenomic patterns for marine turtles. This analysis supports the placement of protostegids outside of Chelonioidea as marine eucryptodirans and establishes Ctenochelys spp. as perhaps some of the earliest representatives of Pan-Cheloniidae.